Effects of achilles tendon immersion in saline and perfluorochemicals on T2 and T2*. Issue 2 (23rd October 2013) - Chang, Eric Y.; Du, Jiang; Bae, Won C.; Statum, Sheronda; Chung, Christine B.
<x xml:space="preserve">Abstract</x> Purpose To determine if immersion of Achilles tendon segments into various solutions improved qualitative delineation of tendon and affected quantitative MR values of T2 and T2*. Materials and Methods Six Achilles tendons were dissected, sectioned (proximal, midportion, and distal tensile pieces) and imaged at 3T both at baseline in air and after immersion into saline, Fomblin, and perfluorooctyl bromide (PFOB), respectively, for 24 h. Blinded readers qualitatively assessed the delineation of tendon boundaries and quantitatively Carr‐Purcell‐Meiboom‐Gill (CPMG) T2 and ultrashort echo time (UTE) T2* was calculated. Comparison between images obtained in air and in solution was made. Results On qualitative evaluation, all images obtained in air had larger air‐tissue susceptibility effects. Mean T2 values of saline, Fomblin, and PFOB groups were 16.1 ± 3.7, 16.6 ± 2.9, and 18.8 ± 2.6 ms at baseline in air, and 14.8 ± 4.6, 15.9 ± 3.0, and 17.7 ± 3.0 ms after immersion in the fluid, respectively. Mean T2* values of saline, Fomblin, and PFOB groups were 2.0 ± 0.8, 1.6 ± 0.5, and 1.5 ± 0.5 ms at baseline in air, and 2.1 ± 0.5, 1.6 ± 0.5, and 1.4 ± 0.5 ms after immersion in the fluid, respectively. There was no significant effect of immersion or fluid type on measured T2 or T2* (P > 0.1). Conclusion These results validate the continued use of these solutions to prevent tendon specimen dehydration and to minimize susceptibility effects. J. Magn. Reson. Imaging 2014;40:496–500. © 2013 Wiley Periodicals, Inc.